Frequência de sarcopenia e seus fatores associados em pessoas vivendo com HIV assistidas por um serviço público no interior do Rio Grande do Sul - Almeida, Luciana Leiria de (2019)
With the increase in life expectancy and the reduction in mortality observed in people with Human Immunodeficiency Virus (HIV) and / or Acquired Human Immunodeficiency Syndrome (AIDS), chronic diseases are being diagnosed earlier and earlier. Sarcopenia is an increasingly diagnosed condition and is associated with risk of bone fractures, decreased quality of life and death. Few studies assess the presence of sarcopenia in people living with HIV (PLHIV). The aim of our study was to evaluate the frequency of sarcopenia and the possible factors associated with it in PLHV older than 50 years. For this purpose, a cross-sectional study was conducted that included PLHV aged 50 years or older and who were registered at the pharmacy of the University Hospital of Santa Maria (HUSM) / RS - Brazil. A structured questionnaire was applied, blood sample was collected, muscle strength was measured, body composition was measured and spine X-ray was performed. Of the 101 patients recruited for the study, 83 underwent both Dual-energy X-ray Absorptiometry (DXA) and muscle strength measurements. The frequencies of sarcopenia and presarcopenia in the individuals studied were 12% and 16.9%, respectively. Low appendicular lean mass (ALMI) was associated with a lower Tscore in all studied sites (spine, femoral neck and total femur). There was a tendency for individuals with sarcopenia to have multiple vertebral fractures more often compared to the rest of the group (44.4% vs. 16.2%, p = 0.066). In the univariate analysis, low ALMI was associated with nitric oxide (NOx) (p = 0.011) and alanine aminotransferase (ALT) (p = 0.040). There was a tendency for higher C-reactive protein (CRP) in patients with low ALMI (p = 0.058). In the multiple linear regression analysis, both ALT (p = 0.047) and CRP (p = 0.009) were associated with low ALMI. In conclusion, as in the general population, sarcopenia appears to be associated with lower bone density and a higher frequency of fractures. The association between low ALMI and CRP suggests that there may be some chronic inflammation component associated with low muscle mass in these individuals.